KPC-2-producing Enterobacterales from ready-to-eat food to hospitalized patients - Venâncio de Godoy, Bianca Lara; do Valle Barroso, Marlon; Fontoura de Azeredo Lourenção, Yasmin; de Andrade, Letícia Kellen; Tosta Rodrigues, Vitória Gabriela; Atuí, Caroline; do Valle, Ana Caroline; Ferreira, Taís Paulino [UNESP]; Nogueira, Mara Corrêa Lelles; Casella, Tiago (Elsevier, 2024)
Foodstuffs are a well-documented source of multidrug-resistant bacteria, and hospitalized patients are usually susceptible to hospital infections owing to their immune status. Therefore, this study aimed to investigate the presence of beta-lactamase-producing Enterobacterales in ready-to-eat foods consumed by hospitalized patients. For this purpose, 51 vegetable and meat samples were collected over 2 months and analyzed. Enterobacterales isolates were identified and subjected to antimicrobial susceptibility testing, followed by beta-lactamase gene screening, pH tolerance assays, and whole-genome sequencing (WGS). Isolates harboring genes encoding extended-spectrum beta-lactamases, cephalosporinases, or carbapenemases were detected, and all isolates tolerated pH levels similar to those in the human gastrointestinal tract. The blaKPC-2 carriers were characterized by WGS and lineages closely related to those causing human infections were identified. These results showed that dietary intake is an alternative route for the transmission of antimicrobial-resistant bacteria, which must be considered when designing effective strategies for infection control.
Keywords: Brazil; Carbapenemase; ESBL; Food